Effects of Lumacaftor-Ivacaftor Therapy on Cystic Fibrosis Transmembrane Conductance Regulator Function in Phe508del Homozygous Patients with Cystic Fibrosis - Gräber, Simon Y.; Scheuermann, Heike; Hirtz, Stephanie; Mairbäurl, Heimo; Mall, Marcus A. (American journal of respiratory and critical care medicine, 2018)
Rationale: The combination of the CFTR (cystic fibrosis transmembrane conductance regulator) corrector lumacaftor with the potentiator ivacaftor has been approved for the treatment of patients with cystic fibrosis homozygous for the Phe508del CFTR mutation. The phase 3 trials examined clinical outcomes but did not evaluate CFTR function in patients.Objectives: To examine the effect of lumacaftor-ivacaftor on biomarkers of CFTR function in Phe508del homozygous patients with cystic fibrosis aged 12 years and older.Methods: This prospective observational study assessed clinical outcomes including FEV1% predicted and body mass index, and CFTR biomarkers including sweat chloride concentration, nasal potential difference, and intestinal current measurement before and 8-16 weeks after initiation of lumacaftor-ivacaftor.Measurements and Main Results: A total of 53 patients were enrolled in the study, and 52 patients had baseline and follow-up measurements. After initiation of lumacaftor-ivacaftor sweat chloride concentrations were reduced by 17.8 mmol/L (interquartile range [IQR], −25.9 to −6.1; P < 0.001), nasal potential difference showed partial rescue of CFTR function in nasal epithelia to a level of 10.2% (IQR, 0.0-26.1; P < 0.011), and intestinal current measurement showed functional improvement in rectal epithelia to a level of 17.7% of normal (IQR, 10.8-29.0; P < 0.001). All patients improved in at least one CFTR biomarker, but no correlations were found between CFTR biomarker responses and clinical outcomes.Conclusions: Lumacaftor-ivacaftor results in partial rescue of Phe508del CFTR function to levels comparable to the lower range of CFTR activity found in patients with residual function mutations. Functional improvement was detected even in the absence of short-term improvement of FEV1% predicted and body mass index.Clinical trial registered with www.clinicaltrials.gov (NCT02807415).